Radical surgery in gynecologic cancer - Esteves Flores, Luis (2015)
The problem of radical surgery in gynecological cancer was presented by Dr. Luis Esteves in relation to the casuistry and experience in the Dept. Of Obstetrics INEN of which he is chief from 1952 to 1959; after which he believed a duty to inform the society and gynecologists colleagues in general, the work accomplished in that period of seven years. This made the work refers exclusively to surgical treatment, noting that the radical and ultra-radical pelvic surgery cancer in women was introduced in our country, for him, with the cooperation of Dr. Castiellano in 1952. He also placed on record also in other centers, especially in the service of gynecology Pab 5 II Loayza Hospital, after other gynecologists grown in limited aspects of such radical surgery.